ВПЛИВ ПУЛЬСАЦІЙ СИГНАЛУ БЕЗКОНТАКТНОГО МАГНІТОЕЛЕКТРИЧНОГО ТАХОГЕНЕРАТОРА НА НАЛАШТУВАННЯ СЛІДКУЮЧОЇ СИСТЕМИ - Акінін, К.П.; Кіреєв , В.Г.; Петухов, І.С.; Філоменко , А.А. (Інститут електродинаміки НАН України, Київ, 2025)
The paper is devoted to the study of operating modes and features of tuning of a servo system containing a brushless magnetoelectric tachogenerator in the angular speed control loop of an executive motor. Features of tuning of the internal loop of angular speed for compensation of electromechanical time constant taking into account pulsations of the tachogenerator signal are studied. Dependences of the signal ripple coefficient at the tachogenerator filter output, the values of the signal ripple swing in the angular speed loop and the effective current value on the parameters of the system operation mode are given. The influence of the system tuning parameters on the performance indexes of angular speed control is studied. The approach to tuning of the servo system taking into account the parameters of the angular speed loop while providing a given stability margin in phase is considered. The results of studies of the servo system are given. References 16, figures 15, table 1.